2021
DOI: 10.1186/s12904-021-00753-y
|View full text |Cite
|
Sign up to set email alerts
|

“It’s given me confidence”: a pragmatic qualitative evaluation exploring the perceived benefits of online end‐of‐life education on clinical care

Abstract: Background Hospital admissions for end-of-life care are increasing exponentially across the world. Significant numbers of health professionals are now required to provide end-of-life care with minimal training. Many health professionals report they lack confidence to provide this care, particularly those in acute hospital settings. This study explored the perceived benefits of online education on health professionals’ capacity to provide end-of-life care. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 51 publications
1
9
0
1
Order By: Relevance
“… 29 These results further support the positive impact of EOLE module learning. 4 20 30 More importantly, addressing the aim of this evaluation, learners from these varied disciplines demonstrated statistically significant improvement of self-perceived EOL care knowledge, skills, attitude and confidence, and reported a high level of intention to change their practice after completion of the module learning, suggesting that all HCPs could benefit from EOLE education regardless of their discipline. These results demonstrated the suitability of EOLE education modules for all HCPs as a quality education course which are consistent with the scope and aim of EOLE project.…”
Section: Resultsmentioning
confidence: 88%
“… 29 These results further support the positive impact of EOLE module learning. 4 20 30 More importantly, addressing the aim of this evaluation, learners from these varied disciplines demonstrated statistically significant improvement of self-perceived EOL care knowledge, skills, attitude and confidence, and reported a high level of intention to change their practice after completion of the module learning, suggesting that all HCPs could benefit from EOLE education regardless of their discipline. These results demonstrated the suitability of EOLE education modules for all HCPs as a quality education course which are consistent with the scope and aim of EOLE project.…”
Section: Resultsmentioning
confidence: 88%
“…A noticeable advantage of the programme was the participants' ability to access information in their own time and place of choosing. E-learning has been well documented in the literature for its convenience and flexibility ( Morgan et al, 2021 ; Suliman et al, 2021 ; Jowsey et al, 2020 ). It is a mode of education that is particularly suitable to community nursing, where nurses work unsociable hours, across large geographical areas, and therefore are more amenable to learning outside of the traditional 9–5 h ( Uprichard, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The short 1-hour structure appealed to participants. This was unsurprising as short periods of teaching are noted to be easily digestible, where information is kept succinct and focused on the topic ( Chicca, 2021 ; Morgan et al, 2021 ; Jowsey et al, 2020 ). E-learning also increases access to education for a wider cohort of learners than could attend an in-person event, as there is no class limit on the number of participants that may attend a session ( Ramsden et al, 2021 ; Uprichard, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…For qualitative data analysis, a pragmatic analysis approach will be adopted by using inductive thematic analysis. 43 44 One researcher will identify recommendations in the transcripts and extract, cumulate and summarise them into a document. Afterwards, relevance and wording of all recommendations will be discussed in the research team until consensus is found.…”
Section: Discussionmentioning
confidence: 99%
“…The online workshop will be audio-recorded and transcribed verbatim. For qualitative data analysis, a pragmatic analysis approach will be adopted by using inductive thematic analysis 43 44. One researcher will identify recommendations in the transcripts and extract, cumulate and summarise them into a document.…”
Section: Discussionmentioning
confidence: 99%